Analisis Faktor Yang Mempengaruhi Kejadian Stunting Pada Balita (Studi Pada Balita Usia 24 – 59 Bulan Desa Batu Putih Kecamatan Taliwang Sumbawa Barat) - Ermawati, Ermawati; Zulfikar, Taufik; Malik, Rahadian (Innovative: Journal Of Social Science Research, 2024)
This study aims to evaluate various factors influencing the incidence of stunting in children aged 24-59 months in Batu Putih Village, Taliwang District, West Sumbawa Regency. Stunting is a serious health issue that can impact cognitive, motor, and language development in children, as well as increase the risk of degenerative diseases in the future. Using a quantitative approach and a cross-sectional design, the study involves 110 selected children. Data were collected through interviews with parents and physical measurements of the children. Data analysis was conducted using bivariate and multivariate tests to assess the relationship between nutritional intake, history of infectious diseases, immunization status, and environmental sanitation conditions with the incidence of stunting. The study reveals a significant link between adequate intake of animal protein and staple foods with the incidence of stunting. Children who do not receive enough animal protein have a 2.4 times higher risk of stunting, while those with insufficient carbohydrate intake face a 1.5 times greater risk. Conversely, there was no significant relationship found between environmental sanitation and history of infectious diseases with stunting. Family income also plays a significant role, with low-income families experiencing a 4.6 times higher risk of stunting. Although immunization status did not show a significant correlation, it remains important to consider as it may be influenced by other factors such as parenting practices and access to nutritious food. The study concludes that improving nutritional intake, especially animal protein and carbohydrates, as well as enhancing family economic conditions, is crucial in reducing stunting. The research recommends targeted, sensitive, integrated, and sustainable interventions to address the stunting issue in the area. Keywords: Stunting, Nutritional Intake, Animal Protein, Carbohydrates, Environmental Sanitation, History of Infectious Diseases, Family Income, Immunization